Perceptions of government guidance and citizen responses during the COVID-19 pandemic: A cross-country analysis - Cervantée E.K. Wild; Maria Inês Gandolfo Conceição; Miho Iwakuma; Sasha Lewis-Jackson; Rie Toyomoto; Alicia Regina Navarro Dias de Souza; Vinita Mahtani-Chugani; Rika Sakuma Sato; Tanvi Rai (Elsevier, 2023)
The public perception of government approaches to pandemic management has played an important role in citizen responses to the COVID-19 pandemic. Although the state and associated health institutions should feasibly be sources of epistemic authority, the pandemic has undermined their legitimacy as anti-science rhetoric proliferated and 'fake news' spread rapidly. In this paper, we present a comparative analysis of interviews with citizens across four different countries and explore how a lack of consistency and clarity in public health guidance from government and other trusted institutions led to a polarisation in public perceptions and mixed understandings of the pandemic. Using interview data collected across Brazil, Japan, Spain and the United Kingdom, we explored whether there were differences in the extent to which both state governments and scientific institutions were perceived as epistemic authorities through managing the pandemic. Participants grappled with a distrust of government guidelines, finding alternative sources of information to manage perceived infection risk, and make decisions around self-medication. Our analysis suggests several components were key to maintaining trust - and therefore epistemic authority - during the pandemic: reliability of the information delivered by different government bodies, including clarity of messaging; reliability of the government bodies themselves, including whether officials conducted themselves appropriately; and honesty about claims to expertise, including communicating when the scientific evidence was unclear or inconclusive. Our data suggests that honest communication about the limits of their knowledge would assist governments in engendering trust among citizens, and theoretically, compliance with public health guidelines.